Implementasi Kebijakan Pengelolaan Sampah di Kawasan Pesisir Kabupaten Tanjung Jabung Timur Provinsi Jambi - Sagala, Irmawati (KAMBOTI: Jurnal Sosial dan Humaniora, 2023)
Tanjung Jabung Timur Regency has a coastline of 230.90 Km, 83.5% of Jambi Province's coastline, which stretches across five of its eleven districts. This coastline has estuaries and swampy areas that cause this area to be challenging to reach by land transportation. This article discusses the waste management program in the coastal area of Tanjung Jabung Timur Regency. The research used a qualitative-analytic method with data collection techniques including document studies, interviews, and observations conducted in the district capital and six villages in three coastal districts. The study shows that the Tanjung Jabung Timur Regency Environmental Service has implemented a waste management program but has yet to reach the coastal areas. The main problem is the limited human resources at the Environment Service and the need for support structures in sub-districts and villages. In addition, it is difficult to transport waste from the coast due to geographical conditions. The lack of public awareness exacerbates this obstacle to protecting the environment. Therefore, a more intensive literacy program is needed to increase public awareness. In addition, it is necessary to have a village-scale waste management policy to be more effective in its implementation.